2021
DOI: 10.1002/jac5.1472
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perceptions of pharmacy students and pharmacists with a community pharmacy‐based objective structured clinical examination

Abstract: Introduction Self‐care therapeutics teaches students how to apply the Pharmacists' Patient Care Process to determine if a patient's concern is appropriate for self‐care and then independently prevent, diagnose, and treat the condition. Objective structured clinical examinations (OSCEs) have been shown to be a reliable and valid form of assessment used in pharmacy education. There is limited research examining the use of a community pharmacy‐based OSCE to evaluate self‐care clinical skills in first year pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…This is consistent with the results of other studies (21,26,33,43,44). For example, results from a study evaluating the use of a community pharmacy-based OSCE to consider self-care clinical skills in first-year pharmacy students in the school of pharmacy University of Arizona (USA) showed that the majority of students believed that OSCE exam was fair, covers a wide clinical wide range of vital clinical skills and that OSCE exam provided a practical experience and valuable learning opportunity (43). Also, results from another study showed that most students believed that OSCE exam was fair, covered the necessary knowledge and competencies, and that OSCE exam was welladministered and well-organised (21).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the results of other studies (21,26,33,43,44). For example, results from a study evaluating the use of a community pharmacy-based OSCE to consider self-care clinical skills in first-year pharmacy students in the school of pharmacy University of Arizona (USA) showed that the majority of students believed that OSCE exam was fair, covers a wide clinical wide range of vital clinical skills and that OSCE exam provided a practical experience and valuable learning opportunity (43). Also, results from another study showed that most students believed that OSCE exam was fair, covered the necessary knowledge and competencies, and that OSCE exam was welladministered and well-organised (21).…”
Section: Discussionsupporting
confidence: 94%
“…However, less than a quarter of pharmacy students thought that OSCE exam was not fair, very intimidating, and required more time. This is consistent with the results of other studies (21,26,33,43,44). For example, results from a study evaluating the use of a community pharmacy-based OSCE to consider self-care clinical skills in first-year pharmacy students in the school of pharmacy University of Arizona (USA) showed that the majority of students believed that OSCE exam was fair, covers a wide clinical wide range of vital clinical skills and that OSCE exam provided a practical experience and valuable learning opportunity (43).…”
Section: Discussionsupporting
confidence: 88%
“…Case studies and role-play activities were provided to the students to practice applying the content to a “real-life” patient. In 2018, students were given an Objective Structured Clinical Examination (OSCE) to assess their knowledge in which the majority of students and facilitators agreed that the OSCE provided a true measure of essential clinical skills required to assess and provide self-care to patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%